Radially symmetric growth of necrotic tumors and connection with nonnecrotic tumors. (December 2019) - Wu, Junde; Wang, Chen
Abstract: In this paper we study a nonlinear free boundary problem for radially symmetric growth of tumors with necrosis. We show this problem is globally well-posed and find a threshold value σ ∗ > 0, such that if and only if external nutrient supply σ ̄ ≥ σ ∗, there exists a unique necrotic stationary solution. We prove it is globally asymptotically stable. For σ ̄ < σ ∗, asymptotic behavior of transient solution has been studied. The connection and mutual transition between necrotic and nonnecrotic tumors are also given.